Ontyczny i etyczny aspekt kosmoekologicznej koncepcji Świata - Korpikiewicz, Honorata (ETHICS IN PROGRESS, 2014)
In this article I provide a summary of insights on the discipline of cosmoecology. I point out the most important cosmic influences on life on Earth, which justifies the hypothesis of Gaia-Uranos. I consider what kind of features must have characterized the cosmic environment in order for life to evolve in this part of the Universe. The problem of physical parameters of the cosmic environment, necessary for the existence of life, has been recognized for centuries; these considerations find their apogeum in the anthropic principle. Here, I discuss the general features of the cosmic universe: harmony, diversity, non-balance, and the rhythms of phenomena. This perspective on the development of the life on Earth influences the understanding of the human place in the universe, among others creations of nature, through the lens of holistic and pathocentric ethics